1985
DOI: 10.1002/chin.198525203
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: SYNTHESIS AND REACTIONS OF 2,5‐DIHYDROXY‐3,4,6,7‐TETRACHLOROCOUMARAN

Abstract: Behandeln des Trichlorbenzochinons (I) mit HCl führt zu dem Tetrachlorcumaran (II), dessen Struktur aus 1H‐ und 13C‐NMR‐Daten hervorgeht.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In previous work [3], we showed that the synthesis of 4H-1,3,4-thidiazines is often complicated by the formation of cyclization sideproducts though we were unable to correlate the formation of any of these products with the structure of the starting compounds.…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…In previous work [3], we showed that the synthesis of 4H-1,3,4-thidiazines is often complicated by the formation of cyclization sideproducts though we were unable to correlate the formation of any of these products with the structure of the starting compounds.…”
mentioning
confidence: 76%
“…Dihydrobenzofuran 1 is the cyclic form of the o-hydroxyphenyl derivative of α-chloroacetaldehyde [3,4]. The major products of the reactions between 1-substituted thiosemicarbazides and α-halocarbonyl compounds are derivatives of 4H-1,3,4-thiadiazine [5].…”
mentioning
confidence: 99%
“…Here, during construction of the heterocycle 2,5-dihydroxy-3,4,6,7-tetrachloro-2,3-dihydrobenzo[b]furan 73 is used as universal synthon (the 2,3-trans configuration predominates). This is the cyclic tautomeric form of the aryl-substituted α-chloroacetaldehyde and is formed in the reaction of vinylquinone 72 with HCl in dioxane solution [78]. The heterocycle was constructed by the reaction of benzofuran 73 with bifunctional nucleophilic reagents.…”
mentioning
confidence: 99%